E-Procurement Practices and Procurement Performance of Insurance Firms in Kenya - Ndwiga, Faith Whitney Murugi; Mutia , Rebecca (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to examine the influence of e-procurement practices specifically electronic tendering, electronic ordering, electronic sourcing, and electronic invoicing on procurement performance among insurance firms in Kenya. Grounded in Transaction Cost Theory, Resource-Based View Theory, Diffusion of Innovations Theory, and the Technology Acceptance Model, the study was guided by the premise that the integration of technology-driven procurement systems can significantly improve operational efficiency and accountability in procurement processes. Methodology: A descriptive survey design was employed, targeting 63 insurance firms registered with the Insurance Regulatory Authority. Data were collected through structured questionnaires administered to procurement managers, and both descriptive and inferential statistics were used to analyze the findings. Findings: The study revealed that e-procurement practices collectively enhance procurement performance by improving efficiency, reducing transaction costs, and promoting transparency in procurement operations. Specifically, electronic tendering, electronic ordering, and electronic sourcing were found to have a positive and significant influence on procurement performance, indicating their critical role in improving procurement speed, supplier relations, and cost control. While electronic invoicing also demonstrated a positive influence, its impact was relatively modest, suggesting a need for improved integration and user adoption. The study concludes that the adoption and effective utilization of e-procurement practices significantly contribute to enhanced procurement performance in the insurance sector. Unique Contribution to Theory, Practice and Policy: By embracing comprehensive e-procurement systems, insurance firms can strengthen operational efficiency, ensure compliance, and improve service delivery. The study recommends that insurance firms invest in robust digital infrastructure, staff training, and continuous system upgrades to fully leverage the benefits of e-procurement in achieving strategic procurement excellence.